2012
DOI: 10.1016/j.jsps.2011.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Ethosomes and ultradeformable liposomes for transdermal delivery of clotrimazole: A comparative assessment

Abstract: THE OBJECTIVE OF WORK WAS TO FORMULATE, EVALUATE AND COMPARE THE TRANSDERMAL POTENTIAL OF NOVEL VESICULAR NANOCARRIERS: ethosomes and ultradeformable liposomes, containing clotrimazole (CLT), an anti-fungal bioactive. The ethosomal formulation (ET4) and ultradeformable liposomal (UL) formulation (TT3) showed highest entrapment 68.73 ± 1.4% and 55.51 ± 1.7%, optimal nanometric size range 132 ± 9.5 nm and 121 ± 9.7 nm, and smallest polydispersity index 0.027 ± 0.011 and 0.067 ± 0.009, respectively. The formulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(67 citation statements)
references
References 38 publications
1
64
0
1
Order By: Relevance
“…70,87 Table 5 summarizes a review of several drugs reported for transdermal delivery using ELs and recently reported new ELs. [88][89][90][91][92][93][94][95][96][97][98] Furthermore, these latest ELs were tabulated (Table 6) with valuable information, such as definition, composition, classification, advantages, and inherent limitations. 14 …”
Section: Local Anesthetic Drugsmentioning
confidence: 99%
“…70,87 Table 5 summarizes a review of several drugs reported for transdermal delivery using ELs and recently reported new ELs. [88][89][90][91][92][93][94][95][96][97][98] Furthermore, these latest ELs were tabulated (Table 6) with valuable information, such as definition, composition, classification, advantages, and inherent limitations. 14 …”
Section: Local Anesthetic Drugsmentioning
confidence: 99%
“…Multilamellar liposomal vesicles were prepared by thin film casting method as reported previously (18), with slight modifications. Briefly, phosphatidylcholine (soya PC) and cholesterol (CH) in 7:3 proportions were dissolved in minimum quantity of chloroform/methanol (3:1; v/v) in round bottom flask (RBF).…”
Section: Preparation Of Liposomes (Lip)mentioning
confidence: 99%
“…In vitro release profile of entrapped drug from different drug-loaded formulations (DTX-LIP, DTX-NP, DTX-DEN, DTX-CNTs) was studied at pH 4 and 7.4 (PBS (pH 7.4 and 4.0): ethanol (7:3) v/v) using dialysis tube diffusion technique (18,32,35). Briefly, drug-loaded formulations were taken into dialysis tubing (MWCO 1-2 kDa, Sigma, India), hermetically sealed from both sides, dipped inside release medium placed on magnetic stirrer (Remi, Mumbai, India) maintained at 37± 0.5°C.…”
Section: Drug Release Studiesmentioning
confidence: 99%
“…Ethosomes possess elevated encapsulation competence for a broad range of molecules including lipophilic drugs (Valjakka et al, 1998). Ethosomes bears an influential advantage of successfully delivering the therapeutic agents deeply across the highly conformational and densely packed lipid bilayers of the stratum corneum (SC) by reducing transition temperature (T m ) of SC fluids, increasing their fluidity and by increasing the membrane permeability by the intercalation of polar head group (Maheshwari et al, 2012). Ethosomes provides high patient compliance as they can be formulated in semisolid dosage forms (Gel or Cream) in contrast to complications associated with iontophoresis and phonophoresis (Simonsson et al, 2011).…”
Section: Merits Of Ethosomesmentioning
confidence: 99%